« Le strabisme effrayant du doute est dans mon œil » : comment regarder les religions romantiques ? - Esther Pinon (Cahiers d'Études du Religieux- Recherches Interdisciplinaires)
Studying religion in Romantic literature raises difficulties which are specific to an age tormented by doubt. How can one grasp without restricting it the infinite diversity of a movement that voices its own spiritual dismay ? After considering ontological and rhetorical answers (substituting the notion of the sacred for religion and questioning texts as literary constructions), this study will attempt to turn doubt itself into the mainspring of a fruitful interpretation : as long as it is chosen and accepted, the “dreadful squint” of Victor Hugo’s owl may be a paradoxical means of achieving better sight.